English Teaching in Rural Government Schools of Karnataka — A Longitudinal Study - Vaijayant, K. (THE PRIMARY TEACHER, 2016)
This paper is the outcome of an evaluation study of an English programme called Swalpa English, Thumba Fun (SETF), designed and implemented for three consecutive years — 2012–13, 2013–14 and 2014–15 — as a large-scale, multi-year initiative by Akshara Foundation, an NGO in Karnataka. The programme was implemented in 576 government primary schools of three most backward educational blocks in Karnataka. The programme’s goal was to empower teachers of grades I to IV with resourceful strategies to teach English to children. It sought to establish, in accordance with the suggestions of the National Curriculum Framework (NCF)–2005, an environment that facilitates English learning in classrooms through fun-filled, exploratory understanding. Akshara Foundation’s research team conducted a longitudinal study based on a controlled before-and-after research design to examine the impact of the intervention by analysing students.